Cough in exercise and athletes - Boulet, L.-P.; Turmel, J. (Pulmonary Pharmacology & Therapeutics, 2019)
In the general population, particularly in individuals with asthma, cough is a common symptom, often reported after exertion, although regular exercise may be associated with a reduction in the prevalence of cough. In athletes, exercise-induced cough is also a particularly frequent symptom. The main etiologies of cough in athletes are somewhat similar to non-athletes, including asthma/airway hyperresponsiveness, upper airways disorders such as allergic or non-allergic rhinitis, and exercise-induced laryngeal obstruction, although these conditions are more frequently observed in athletes. In these last, this symptom can also be related to the high ventilation and heat exchange experienced during exercise, particularly during exposure to cold/dry air or pollutants. However, gastroesophageal reflux, a common cause of cough in the general population, despite being highly prevalent in athletes, has not been reported as a main cause of cough in athletes. Cough may impair quality of life, sleep and exercise performance in the general population and probably also in athletes, although there are few data on this. The causes of cough should be documented through a systematic evaluation, the treatment adapted according to identified or most probable cough etiology and pattern of presentation, while respecting sports anti-doping regulations. More research is needed on exercise-induced persistent cough in the athlete to determine its pathophysiology, optimal management and consequences.